PERKEMBANGAN ANALISIS FITOLIT DAN PENERAPANNYA DALAM ARKEOLOGI DI INDONESIA - Aldhi Wahyu Pratama (Forum Arkeologi, 2020)
Nowadays, the method of analysis in archaeology is growing, including the archaeobotany approach by using phytolith analysis. Apart from other microbotany data such as pollen and starch, phytolith has the advantage of being able to survive in the soil under fairly extreme conditions. Phytolite analysis is still rarely used in Indonesia for reconstructing the past environment,. Meanwhile, it has been used in other scientific researches such as paleoclimatology, paleoecology, paleoethnobotany. The purpose of this research is to explain phytolith as archaeological data and its implementation in archeology in Indonesia. This research data focuses on reviews of several studies which have used phytolith data as archaeological data in the world, including in Indonesia. Based on the results of archaeological research using phytolith data in this paper, it can provide an overview of the past environment, plant use, and human dietary patterns. Research prospects using phytolith analysis in Indonesia are still wide open which is also described in this paper. Metode analisis dalam arkeologi dewasa ini semakin berkembang, termasuk pendekatan arkeobotani dengan menggunakan analisis fitolit. Selain data mikrobotani lain seperti polen dan starch, fitolit memiliki keuntungan tersendiri yang mampu bertahan di dalam tanah dengan kondisi yang cukup ekstrim. Namun, di Indonesia sendiri analisis fitolit dalam arkeologi relatif sedikit digunakan dalam upaya rekonstruksi lingkungan masa lalu. Sementara itu fitolit telah digunakan dalam penelitian ilmu lain seperti paleoklimatologi, paleoekologi, paleoetnobotani. Tujuan dari penelitian ini adalah menjelaskan fitolit sebagai data arkeologi dan implementasinya dalam arkeologi di Indonesia. Data penelitian ini berfokus pada ulasan beberapa penelitian di dunia termasuk di Indonesia yang telah menggunakan data fitolit sebagai data arkeologi. Berdasarkan hasil penelitian arkeologi dengan menggunakan data fitolit dalam tulisan ini dapat memberikan gambaran lingkungan masa lalu, pemanfaatan tumbuhan, dan juga pola diet manusia. Selain itu prospek penelitian dengan menggunakan analisis fitolit di Indonesia masih terbuka lebar yang juga dijelaskan dalam tulisan ini.